2010
DOI: 10.1124/mol.109.062836
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Copper Transporter 2 Expression by Copper and Cisplatin in Human Ovarian Carcinoma Cells

Abstract: Down-regulation of copper transporter 1 (CTR1) reduces uptake and sensitivity, whereas down-regulation of CTR2 enhances both. Cisplatin (DDP) triggers the rapid degradation of CTR1 and thus limits its own accumulation. We sought to determine the effect of DDP and copper on the expression of CTR2. Changes in CTR1 and CTR2 mRNA and protein levels in human ovarian carcinoma 2008 cells and ATOX1(ϩ/ϩ) and ATOX1(Ϫ/Ϫ) mouse embryo fibroblasts in response to exposure to DDP and copper were measured by quantitative rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 28 publications
(32 reference statements)
3
45
2
Order By: Relevance
“…[9][10][11][12][13][14][19][20][21][22][23][24] It is widely accepted as the primary mechanism of influx of this platinum-based drug in cells. 10,11 To assess the effect of extracellular copper on this form of drug transport, the surviving fraction and viability ratio of Caco-2 cells was studied by exposing cells to a mixture of 5 µM copper and increasing concentrations of cDDP for 2.5 hours.…”
Section: 38mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][19][20][21][22][23][24] It is widely accepted as the primary mechanism of influx of this platinum-based drug in cells. 10,11 To assess the effect of extracellular copper on this form of drug transport, the surviving fraction and viability ratio of Caco-2 cells was studied by exposing cells to a mixture of 5 µM copper and increasing concentrations of cDDP for 2.5 hours.…”
Section: 38mentioning
confidence: 99%
“…[14][15][16][17] Although some groups report distinct molecular behaviors of the different members of the hCTR family, which appear to be cell-dependent, all reports agree that copper, due to its affinity with the hCTR receptor, affects receptormediated entry of cDDP negatively, resulting in improved cytotoxicity. 9,[18][19][20][21][22][23] Although copper receptors have a critical role in the uptake of cisplatin, one of the first studies that focused on the mechanisms of thermal enhancement of cDDP reported an increase in cell membrane fluidity, which in turn augmented the uptake of cDDP. 17,24,25 Therefore, the synergism of cDDP and hyperthermic treatment can potentially be explained in the context of membrane fluidity.…”
Section: Introductionmentioning
confidence: 99%
“…9,10) The expression of Ctr1 was increased under the Cu-depleted state, whereas that of Ctr2 was markedly suppressed by the Cu depletion. 11,12) Thus, the putative function of Ctr2 may be different from that of Ctr1. Cu-transporting P-type ATPases, i.e., Atp7a and Atp7b, are expressed on the Golgi apparatus and participate in the efflux of Cu from cells.…”
Section: Introductionmentioning
confidence: 99%
“…can be modified after treatment by special compounds, and this is also true for the other two transporters, the P-type transporters ATP7A and ATP7B (78). The mechanism of cisplatin resistance in the A2780cis cells is still not fully determined, therefore, further investigation is required; however, the resistance is supposedly due to a multifactorial mechanism including altered transporter expression patterns, mismatch repair and cell-cycle modification (31).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…in intracellular membranes but also in the nucleus and that exposure to either copper or cisplatin increased the level of CTR2 in the nucleus as well as in the cytoplasm (78 ATP7A is expressed in the intestinal epithelium as well as most other tissues other than liver, and the pathology of X-linked Menkes disease reflects inadequate mobilization of copper from a number of tissues such as intestine, kidney and blood-brain barrier (82)(83)(84)(85).…”
Section: Copper Transporters In Cisplatin Resistancementioning
confidence: 99%